SMART URBAN GOVERNANCE FRAMEWORKS: A COMPARATIVE ANALYSIS - Jarour, Ayah; Mocanu, Mariana (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
In this paper, we present a novel comparative analysis of smart urban governance frameworks, evaluating their effectiveness in improving urban management and service delivery. By examining models such as City as a Platform (CaaP) and Integrated Command and Control Centers (ICCC), the study identifies key strengths, limitations, and best practices in areas like technology integration, data handling, citizen engagement, scalability, sustainability, and resilience. The findings indicate that while these frameworks enhance transparency and operational efficiency through open data and real-time monitoring, they face challenges related to data protection, technological reliability, and ensuring inclusiveness, particularly concerning data privacy and socio-economic inequalities. The paper proposes a theoretical framework that integrates resilience, sustainability, and citizen-focused principles, supported by technologies like blockchain and advanced analytics. The practical relevance of this research lies in its potential to guide policymakers and urban planners in the development of smart cities that are not only technologically advanced but also resilient, inclusive, and truly sustainable. The research advocates for a comprehensive approach to smart governance that balances technological innovation with social equity and environmental responsibility, fostering collaboration among diverse stakeholders to develop resilient and inclusive smart cities.